Cow Manure for Improving Carbon-to-Nitrogen Ratio of Tailings, Growth, and Biomass of Water Kale (Ipomoea reptans Poir.) - Hindersah, Reginawanti; Ardelia, Zahra; Sofyan, Emma Trinurani; Setiawan, Ade; Damayanti, Farida (Jurnal Ilmu Pertanian, 2025)
Gold mine tailings are characterized by low organic matter, poor nutrient availability, extreme pH conditions, and unfavorable texture, all of which restrict plant growth. This study evaluated the effects of cow manure (CM) on soil chemical properties, carbon-to-nitrogen (C/N) ratio, and the growth and biomass of water kale (Ipomoea reptans Poir.) cultivated in tailings-based media. A greenhouse experiment was arranged in a randomized block design consisting of five treatments: 0% (control), 15%, 30%, 45%, and 60% CM (v/v), each replicated six times. Observations included soil pH, organic carbon, total nitrogen, C/N ratio, plant growth parameters, biomass, and microbial populations at 35 days after planting. The application of CM significantly increased organic C, total N, and the C/N ratio, with the highest values observed at 60% CM. However, higher CM doses reduced substrate pH to slightly acidic levels. The 15% CM treatment produced the greatest improvements in plant growth and biomass, increasing plant height by 21%, stem thickness by 29%, leaf number by 8%, and fresh and dry biomass by 73% and 120%, respectively, compared with the control. Increasing CM above 15% enhanced the C/N ratio but did not further improve plant performance, likely due to reduced nitrogen availability associated with higher organic matter and slower mineralization. CM applications did not significantly affect bacterial or fungal populations in the rhizosphere. Overall, the findings indicate that low-dose CM (15%) is optimal for improving the C/N ratio, supporting nutrient availability, and enhancing water kale growth in tailings. This study demonstrates the potential of organic amendments for rehabilitating gold mine tailings and highlights their role in restoring soil functionality and supporting sustainable revegetation efforts.